The public clocks and social unification of time in México City, 1882-1922 (Tzintzun, Revista de Estudios Históricos, 2016)
This research focuses on the debates, conflicts and proposals that generatedaround the proliferation of public clocks in México City between the years 1882and 1922. Despite the proliferation of these machines, the possibilities of citizensto know the exact time was complicated by a number of problems detailed in thetext. Facing these difficulties, scientist, journalists and public officials reacted byasking the unification  of time, that is, the creation of a political and social conven-tion that would establish a single time for all the Mexican capital. The objectiveof this work is to establish the ambiguities and intricacies of this process of timestandardization, due both to state as to civil society interests, and that, at the sametime, involved aspects of positivist modernization while appealing to traditionalelements. Demographic and spatial constitution of México City has been a topicaddressed by historians, however, this research attempts to look at the construc-tion of a temporary experience in the city, which so far has not been explored.
Keywords: public clocks; city; social conventions; urban history